Pengaruh Hiperglikemia Terhadap Mortalitas pada Penderita Stroke Iskemik Fase Akut di Rsud Dr. Moewardi - Susilo, Taufik Adi; , dr. Listyo Asist Ppujarini, M.Sc., Sp.S; , dr. Dona Dewi Niriawati (2015)
Background: Stroke is the second largest cause of death in developed countries and the third largest in the developing countries. One of the factor that caused the death of patients with stroke was diabetes mellitus. The hyperglycemia condition worsens neurologic deficit and would increase mortality. Purpose: The purpose of this research is to know the effect of Hyperglycemia to Mortality in Stroke Ischemic acute sufferer at RSUD Dr. Moewardi. Method: This research was observational analytic non experiment with cross sectional approach. Sample of this research with purposive sampling were stroke ischemic acute patients with a total sample of 86 people. 43 patients of stroke ischemic acute with hyperglycemia and 43 patients of stroke ischemic acute without hyperglycemia at RSUD Dr. Moewardi. The data obtained from range of medical record from January 2014 till November 2015. Analysis statistic using Chi-Square test. Result: Patient stroke ischemic acute with hyperglycemia show that 22 patients passed away (25.5%) 21 patients are alive (24.42%) and patient stroke ischemic acute without hyperglycemia show that 5 patients passed away (5.81%) 38 patients are alive (44.19%). In statistic using Chi-Square test obtained that there is significant correlation between hyperglycemia with mortality patient of stroke ischemic acute, with estimation OR = 7.962; 95% CI = 2.630-24.103 p= 0.000 (p<0.05) with value x2 = 15.602. Conclusion: Based on the analysis data in this research showed that there is influence hyperglycemia with mortality in patient stroke ischemic acute and patient stroke ischemic acute with hyperglycemia has mortality risk 7.962 times than patient stroke ischemic acute without hyperglycemia. Age, hypertension and hypercholesterolemia did not influence of mortality in patient stroke ischemic acute.